2003
DOI: 10.1590/s0073-47212003000200001
|View full text |Cite
|
Sign up to set email alerts
|

Planktonic ciliates Choreotrichida and Strombidiida from the inner zone of Bahía Blanca Estuary, Argentina

Abstract: Seven species of aloricate planktonic ciliates were identified using protargol staining. Lynn & Gilron, 1993; they were collected from the inner zone of the Bahía Blanca estuary in the southern region of the Buenos Aires province, Argentina. These species represent new records to South America (Argentina).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 13 publications
5
25
1
Order By: Relevance
“…This species was also found in the inner zone of Bahia Blanca Estuary, Argentina, where salinity was 29 to 30 psu and temperature 12 to 21°C (Pettigrosso 2003). In the present study, this species was observed to generally be more abundant in Masan Bay than in Onagawa Bay.…”
Section: Vegetative Populationsupporting
confidence: 68%
“…This species was also found in the inner zone of Bahia Blanca Estuary, Argentina, where salinity was 29 to 30 psu and temperature 12 to 21°C (Pettigrosso 2003). In the present study, this species was observed to generally be more abundant in Masan Bay than in Onagawa Bay.…”
Section: Vegetative Populationsupporting
confidence: 68%
“…The PCA results revealed that the biomass of the phytoplankton-aloricate ciliate community in the Bahía Blanca Estuary showed a seasonal variability. At least twenty-four different aloricate ciliate taxa were recorded during the annual cycle in the Bahía Blanca estuary, of which seven were later identified to species level using the protargol staining method (PETTIGROSSO, 2003). The assembly of winter dates consisted of large-sized ciliates preying on blooming diatoms, characterized principally by heterotrophic choreotrichs and mixotrophic oligotrichs belonging to the Strombidinopsis and Strombidium genera.…”
Section: Ciliate and Phytoplankton Biomassmentioning
confidence: 99%
“…The assembly of winter dates consisted of large-sized ciliates preying on blooming diatoms, characterized principally by heterotrophic choreotrichs and mixotrophic oligotrichs belonging to the Strombidinopsis and Strombidium genera. The most conspicuous species were Strombidinopsis elongata (97-129 µm in length, 74-82 µm in width) and the mixotrophic Strombidium emergens (27-39 µm in length, 19.5-30 µm in width) (PETTIGROSSO, 2003). Large species like Cyrtostrombidium sp.…”
Section: Ciliate and Phytoplankton Biomassmentioning
confidence: 99%
See 2 more Smart Citations